PERENCANAAN ULANG VOLUME EMBUNG PUSPORENGGO KECAMATAN MUSUK KABUPATEN BOYOLALI - Joko Susilo; Didik Kurniawan; Totok Apriyanto; Ratih Pujiastuti (Jurnal Teknik Indonesia, 2023)
Pusporenggo Smalldam was built in Pusporenggo Village, Musuk District, Boyolali Regency. This reservoir was built to meet the needs of raw water Pusporenggo Village.The analyzes carried out include: analysis of watershed area, analysis of raw water needs and calculation of reservoir volume. From the analysis, watershed area of Pusporenggo Smalldam  is 0.339 km² with a river length of 1,281 km. Sediment volume: 15,083.61m³, infiltration volume: 26,101.97m³, evaporation volume: 1,436.55m, volume of raw water requirement: 104,407.88m³. From the volume calculation, it is known that the Pusporenggo Reservoir requires a reservoir volume of: 147.030.00m³. As for the initial design, the Pusporenggo Embung is planned with a spillway elevation of +501.50 and a volume of 234.532.60m³. It can be concluded that this reservoir can be used to fulfill water requirement for other areas.e